1998
DOI: 10.1159/000025583
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Endothelin-1 and ET<sub>A</sub> and ET<sub>B</sub> Receptors in Human Cirrhosis: Relationship with Hepatic Hemodynamics

Abstract: Previous experimental studies have suggested that the paracrine endothelin system may participate in the regulation of hepatic hemodynamics in cirrhosis. The present study assesses the relationship between increased portal pressure and preproET-1, ETA receptor and ETB receptor gene expression in human cirrhosis. PreproET-1, ETA receptor and ETB receptor mRNA abundance was estimated by quantitative PCR in human hepatic tissue from subjects with normal liver and in cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
58
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 22 publications
1
58
0
2
Order By: Relevance
“…Previous endothelin studies that investigated this issue mainly focused on the resistance of portal vein or intrahepatic vasculature. 5,[13][14][15]30 Recently, indirect evidence regarding the effect of ET-1 on the collateral vascular resistance was reported by Sogni et al 15 They found that in vivo infusion of bosentan, a mixed ET A and ET B receptor antagonist, significantly reduced the portal pressure and hepatocollateral resistance in PVL and cirrhotic rats. 15 Because bosentan had no effect on the intrahepatic vascular resistance in normal rats, they proposed that in PVL rats bosentan must decrease the collateral vascular resistance.…”
Section: Discussionmentioning
confidence: 97%
“…Previous endothelin studies that investigated this issue mainly focused on the resistance of portal vein or intrahepatic vasculature. 5,[13][14][15]30 Recently, indirect evidence regarding the effect of ET-1 on the collateral vascular resistance was reported by Sogni et al 15 They found that in vivo infusion of bosentan, a mixed ET A and ET B receptor antagonist, significantly reduced the portal pressure and hepatocollateral resistance in PVL and cirrhotic rats. 15 Because bosentan had no effect on the intrahepatic vascular resistance in normal rats, they proposed that in PVL rats bosentan must decrease the collateral vascular resistance.…”
Section: Discussionmentioning
confidence: 97%
“…44 Indeed, localization of infused, labeled ET-1 in the liver is consistent with binding to stellate cells. 15,45 Further, endothelin receptors are up-regulated in the injured liver 40,46 and specifically in stellate cells 19 (Fig. 1).…”
mentioning
confidence: 89%
“…Diastolic dysfunction, characterized by an altered pattern of transmitral flow due to impaired diastolic relaxation of left ventricle, can be easily assessed by echocardiography and accordingly can be considered as a marker of this condition. As far as diastolic dysfunction is concerned, many etiological factors have been reliably advocated as potential pathogenic agents: notably substances as NO [18][19][20][21], TNF [22], reactive nitrogen species [23], neurohormones [24][25][26][27][28] may well affect heart structure and function along with circulatory overload [24,29] and overactivity of the SNS [30]. Thickening of heart parietal walls has been reported [12,14,17,31], nevertheless the nature of the structural changes underlying diastolic dysfunction has not been clarified so far.…”
Section: Introductionmentioning
confidence: 99%